Factors affecting the reproductive efficiency in crayfish: implications for aquaculture - Harlioglu, Muzaffer Mustafa; Farhadi, Ardavan (Wiley, 2017)
In recent years, crayfish aquaculture industry has been developing rapidly in different regions of the world. Crayfish aquaculture is often carried out in dams, lakes and extensive pond systems. There is an increasing demand for crayfish juvenile in aquaculture sector. Therefore, it is important to know which factors affect reproductive efficiency in crayfish. In the present review, factors affecting the reproductive efficiency of crayfish are divided into two main sections, external and internal factors. Dietary lipids, phospholipids, highly unsaturated fatty acids, protein and amino acids, vitamins and carotenoids are important external factors affecting broodstock crayfish reproduction. In addition, various external (i.e. female size, stocking density, temperature, photoperiod, sex ratio) and internal (i.e. endogenous hormones) factors affect the reproductive efficiency in crayfish. This study reviews the present knowledge with the purpose of realizing the factors that are important to reach optimal crayfish nutrition, maturation and reproduction (i.e. pleopodal egg number and quality). This review will particularly be useful for crayfish farmers and crayfish hatchery units.
Keywords: broodstock; egg; gonad; hormone; reproduction; nutrition